Eco-Humanistic Politeness and Addressing Strategies in Lecturer-Student WhatsApp Interactions: A Pragmatic Perspective - Lukman , Lukman; Merling , Andi; Haryeni, Haryeni; Hasjim, Munira; Indarwati, Indarwati (Journal of Ecohumanism, 2024)
This study explores politeness strategies in lecturer-student interactions within WhatsApp course groups, addressing concerns related to impoliteness and misunderstandings. Employing a qualitative research using a descriptive method and a pragmatic approach, the research examines approximately 109 WhatsApp text screenshots from three different professor-student groups. Findings reveal eight distinct politeness strategies, following Brown and Levinson's categorization (1987). The findings revealed that Lecturers demonstrate seven linguistic forms of politeness strategies, while students employ three forms to highlighting power dynamics' influence on linguistic choices. The language speech strategies encompassing direct, positive, and negative dimensions, with both lecturers and students frequently using negative speech. It means that Addressing and Politeness Strategies in Lecturer-Student Interaction on the WhatsApp platform include Forms of Addressing: Lecturer-Student (TS), Student-Lecturer (ST), and Student-Student (SS) is Zero Pronouns is the most frequently-used strategy applied by the Lecturers.